2022
DOI: 10.3390/microorganisms10050904
|View full text |Cite
|
Sign up to set email alerts
|

Whole Genome Sequence Analysis of a Novel Apilactobacillus Species from Giant Honeybee (Apis dorsata) Gut Reveals Occurrence of Genetic Elements Coding Prebiotic and Probiotic Traits

Abstract: Apilactobacillus spp. are classified as obligate fructophilic lactic acid bacteria (FLAB) that inhabit fructose-rich niches such as honeybee gut. Lactic acid bacteria are an important component of the gut microbiome and play a crucial role in maintaining gut health. In this study, a new FLAB strain HBW1, capable of producing glucan-type exopolysaccharide, was isolated from giant honeybee (Apis dorsata) gut and subjected to whole genome sequencing (WHS) to determine its health-beneficial traits. The genome size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…Although not evaluated in this study, Al. kunkeei species is capable of synthesising bioactive molecules with prebiotic properties, such as LPS, as mentioned before (Meng et al, 2018;Ahmad et al, 2022). However, none of the nineteen E. hirae isolates from raw cow's milk were able to produce EPS in a previous study by Espeche et al (2012).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Although not evaluated in this study, Al. kunkeei species is capable of synthesising bioactive molecules with prebiotic properties, such as LPS, as mentioned before (Meng et al, 2018;Ahmad et al, 2022). However, none of the nineteen E. hirae isolates from raw cow's milk were able to produce EPS in a previous study by Espeche et al (2012).…”
Section: Discussionmentioning
confidence: 82%
“…It has been reported that Apilactobacillus species, mainly Al. kunkeei, harbour genes encoding glucosyltransferases responsible for the synthesis of prebiotic glucan-type EPS (Meng et al, 2018;Ahmad et al, 2022). Therefore, these factors may be involved in the potential mechanism of the stimulatory effects of Al.…”
Section: Discussionmentioning
confidence: 99%
“…Other bacterial taxa in the honeypot ant microbiome, although comprising a very small percentage, included several genera identified in the core honey bee microbiome including Gilliamella , Apilactobacillus , and Bombella . These are thought play a role in digestion by secreting substances that aid in the metabolism of certain toxic carbohydrates in the nectar diet ( Ahmad et al, 2022 ; Härer, Hilgarth & Ehrmann, 2022 ; Zheng et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The dextran type exopolysaccharide (EPS) synthesizing isolate Apilactobacillus waqarii (HBWI) used in the present study was isolated from honeybee gut ( Apis dorsata ) previously and reported as a novel species [ 75 ].…”
Section: Methodsmentioning
confidence: 99%